Search for Extremely Metal-poor Stars with Gemini-N/Graces. I. Chemical-abundance Analysis - Miji Jeong; Young Sun Lee; Timothy C. Beers; Vinicius M. Placco; Young Kwang Kim; Jae-Rim Koo; Ho-Gyu Lee; Soung-Chul Yang (The Astrophysical Journal, 2023)
We present stellar parameters and abundances of 13 elements for 18 very metal-poor (VMP; [Fe/H] < –2.0) stars, selected as extremely metal-poor (EMP; [Fe/H] < –3.0) candidates from the Sloan Digital Sky Survey and Large sky Area Multi-Object Fiber Spectroscopic Telescope survey. High-resolution spectroscopic observations were performed using GEMINI-N/GRACES. We find 10 EMP stars among our candidates, and we newly identify three carbon-enhanced metal-poor stars with [Ba/Fe] < 0. Although chemical abundances of our VMP/EMP stars generally follow the overall trend of other Galactic halo stars, there are a few exceptions. One Na-rich star ([Na/Fe] = +1.14) with low [Mg/Fe] suggests a possible chemical connection with second-generation stars in a globular cluster. The progenitor of an extremely Na-poor star ([Na/Fe] = –1.02) with high K- and Ni-abundance ratios may have undergone a distinct nucleosynthesis episode, associated with core-collapse supernovae (SNe) having a high explosion energy. We have also found a Mg-rich star ([Mg/Fe] = +0.73) with slightly enhanced Na and extremely low [Ba/Fe], indicating that its origin is not associated with neutron-capture events. On the other hand, the origin of the lowest Mg abundance ([Mg/Fe] = –0.61) star could be explained by accretion from a dwarf galaxy, or formation in a gas cloud largely polluted by SNe Ia. We have also explored the progenitor masses of our EMP stars by comparing their chemical-abundance patterns with those predicted by Population III SNe models, and find a mass range of 10–26 M _⊙ , suggesting that such stars were primarily responsible for the chemical enrichment of the early Milky Way.